Intramedullary Fixation in Adolescent Humerus Fractures: An Overview - Abdul Qayyum Khan; Mohammad Baqar Abbas (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter delves into the intricate management of humeral shaft fractures in adolescents, a distinct and often challenging subset of pediatric fractures. While non-operative approaches have historically yielded excellent results in children, adolescents present unique complexities due to their rapid growth. These challenges may result in complications such as malalignment, angulation, and malrotation, necessitating operative interventions. The traditional approach of open reduction and internal fixation with plates and screws, while effective, is not without its limitations. Soft tissue dissection, scarring, and complications pose concerns, making it imperative to explore alternative techniques. This chapter centers on one such alternative—closed intramedullary K-wire fixation. The method employs stainless steel K-wires introduced into the humeral shaft through minimally invasive techniques, mitigating many drawbacks associated with traditional open procedures. Through a comprehensive examination of the closed intramedullary K-wire technique, this chapter outlines its advantages and clinical outcomes. Notably, this technique minimizes blood loss, preserves the integrity of soft tissues, and maintains the fracture hematoma, thereby fostering early bridging callus formation. The results of a study conducted at Jawaharlal Nehru Medical College & Hospital, AMU, Aligarh, between 2012 and 2014, are presented, demonstrating a 97.5% union rate and minimal complications. In conclusion, closed intramedullary K-wire fixation emerges as a promising alternative for managing adolescent humeral shaft fractures. The technique offers a safe, cost-effective, and efficient approach, ensuring stability while preserving soft tissue integrity. It enables early bridging callus formation, early initiation of physiotherapy, and optimal functional outcomes, making it a valuable addition to the orthopedic surgeon’s toolkit for addressing this challenging fracture type.